2019
DOI: 10.3390/cells8070734
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling Pathways in Osteoarthritic Cartilage Destruction

Abstract: Osteoarthritis (OA) is a type of joint disease associated with wear and tear, inflammation, and aging. Mechanical stress along with synovial inflammation promotes the degradation of the extracellular matrix in the cartilage, leading to the breakdown of joint cartilage. The nuclear factor-kappaB (NF-B) transcription factor has long been recognized as a disease-contributing factor and, thus, has become a therapeutic target for OA. Because NF-B is a versatile and multi-functional transcription factor involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
294
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(306 citation statements)
references
References 217 publications
(271 reference statements)
6
294
0
6
Order By: Relevance
“…Genes in these categories include NF-kB subunits, chemokine receptors, interleukins, MAP kinases, TNF ligands, and other cytokines. This is consistent with previous studies that have demonstrated that FN-f treatment stimulates a proinflammatory response via MAP kinases and NF-κB signaling 15,16,25,41,51 , as well as the established role of inflammation in the progression of OA 24,30,39,40,42,43,47,52,53 . Genes downregulated in response to FN-f were enriched for GO terms for development and morphogenesis and included HOX genes, TGFBR2, and COL8A2, among others.…”
Section: Fn-f Induces Transcription Of Proinflammatory Genes and Pathsupporting
confidence: 93%
See 1 more Smart Citation
“…Genes in these categories include NF-kB subunits, chemokine receptors, interleukins, MAP kinases, TNF ligands, and other cytokines. This is consistent with previous studies that have demonstrated that FN-f treatment stimulates a proinflammatory response via MAP kinases and NF-κB signaling 15,16,25,41,51 , as well as the established role of inflammation in the progression of OA 24,30,39,40,42,43,47,52,53 . Genes downregulated in response to FN-f were enriched for GO terms for development and morphogenesis and included HOX genes, TGFBR2, and COL8A2, among others.…”
Section: Fn-f Induces Transcription Of Proinflammatory Genes and Pathsupporting
confidence: 93%
“…To determine pathways that were affected by FN-f treatment, we identified Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways that were enriched in each of the four gene sets (Fig 4B). Early-response upregulated genes were enriched for TNF and NF-κB pathways, both of which have been implicated in OA and even targeted for therapeutic OA treatments 30,42,54 . Intriguingly, late-response upregulated genes were most strongly enriched for the ferroptosis pathway, a form of programmed cell death dependent on iron and accumulation of lipid peroxides induced by reactive oxygen species, which have been implicated in OA 55 .…”
Section: Fn-f Induces Transcription Of Proinflammatory Genes and Pathmentioning
confidence: 99%
“…This study revealed that NFκB induced catabolic gene expression through NFκB response elements, thereby promoting the expression of major pro-inflammatory and destructive mediators, including cyclooxygenase 2 (COX2), prostaglandin E2 (PGE2), and inducible nitric oxide synthase (iNOS). Particularly, the loss of iNOS appeared to attenuate the process of inflammation [12][13][14]. Interestingly, the data shown in Figure 1A above indicated that LPS-induced NO production in vitro was inhibited in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 85%
“…More importantly, inhibition of NF-κB has been shown to limit the production of proinflammatory cytokines like IL-6 and CXCL10 in mouse models resulting in reduced mortality [34]. Dysregulation of NF-κB activity has been broadly implicated in the production of inflammatory cytokines (TNFα, IL-1β, IL-6) and cell apoptosis [35][36][37]. Also, it has been reported that NF-κB signaling pathways can coordinate with other hallmark pro-inflammatory transcription factors in the immune response [38].…”
Section: Lmwf5a Down-regulates Pro-inflammatory Transcription Factorsmentioning
confidence: 99%